The Relationship between Happiness Index and Academic Achievements of University Students in Xavier Learning Community, Chiang Rai. - Kosanwattana, Sikarin; Kitcharoen, Aphisit; Pongprasertsin, Saranyu; Chaiyadej , Chetha; Saengthien, Pichet; Koochad, Vatcharapol; Prombutr, Jamriang; Samerporn, Angsumalee (Saengtham College Journal, 2023)
The objectives of this survey research are studying the happiness index of University Students in Xavier Learning Community, Chiang Rai and studying the relationship between happiness index and academic achievements of university students in Xavier Learning Community, Chiang Rai. 67 samples of the whole population of 84 university students in Xavier Learning Community, Chiang Rai were recruited through a purposive sampling method. The data has been accumulated through Thai Happiness Indicators (THI-15) questionnaires and academic achievements of university students in Xavier Learning Community, Chiang Rai. Pearson correlation is utilized with descriptive statistics including percentage, mean, and standard deviation. The findings indicated that there is no correlation between the means of happiness index and academic achievements of university students in Xavier Learning Community, Chiang Rai.